Health and nutrition emergency response among internally displaced persons at Ranch collective site, Chagni, Ethiopia: The role of emergency operation center, lessons from the field, and way forwards - Tefera Alemu; Belay Bezabih; Abraham Amsalu; Eyaya Hassen; Mahteme Haile; Melkamu Abite (Frontiers Media S.A., 2022)
BackgroundIn October 2020, about 79,041 ethnically Amhara/Agew people had been internally displaced (IDPs) from Metekel zone of Benishangul-Gumuz region and lived in Ranch collective site, Chagni town, Ethiopia. Onsite PHEOC met the health and nutrition needs of the IDPs as per international humanitarian response standards.MethodsOn January 11/2021, the Amhara Public Health Institute (APHI) established an onsite Public Health Emergency Operation Center (PHEOC) at Ranch collective site. Health workers and vehicles were deployed. A temporary clinic having nine outlets was built. Drugs and medical supplies were mobilized from different sources. The overall response period lasted about 8 months, from December 2020 up to June 2021.ResultsA total of 33,410 IDPs had received free essential health services. Mental health and psychosocial support services had been given for 1,803 cases. Specialized medical services such as trachomatous trichiasis (30), cataract surgery (8) and sputum samples for mycobacterium tuberculosis (120) have been done. Moreover, 454 women received antenatal care services and 137 women gave birth at health facilities. About 837 children have got measles supplementary dose and 1,280 adults took a COVID-19 vaccination. A total of 1,448 children under five, 454 pregnant and 402 lactating women had been screened on monthly basis. Of which, severe and moderate malnutrition rate was 46 (3.2%) and 75 (5.2%), respectively. A total of 194 trench latrine seats, 74 shower rooms and 50 hand washing facilities had been constructed. There were no human feces present nor solid wastes accumulated around the shelters or settlements. Both active and passive surveillance activities were carried out throughout the camp life. We also conducted regularly Risk Communication and Community Engagement activities on priority health issues.ConclusionWe adequately met the health and nutrition needs of the IDPs as stated in the Sphere humanitarian handbook. We sought to have a strong Incident Management System and coordination platforms like PHEOC, a resilient health system, a training curriculum called Leading in Emergencies, and a multipurpose collective center with infrastructures, humanitarian response guidelines, training materials, and risk/vulnerability-based preparedness plan.